Cerebrovascular reactivity measurements using 3T BOLD MRI and a fixed inhaled CO2 gas challenge: Repeatability and impact of processing strategy - Sleight, Emilie; Stringer, Michael S.; Mitchell, Isla; Murphy, Madeleine; Marshall, Ian; Wardlaw, Joanna M.; Thrippleton, Michael J. (Frontiers in Physiology, 2023)
Cerebrovascular reactivity (CVR) measurements using blood oxygen level dependent (BOLD) magnetic resonance imaging (MRI) are commonly used to assess the health of cerebral blood vessels, including in patients with cerebrovascular diseases; however, evidence and consensus regarding reliability and optimal processing are lacking. We aimed to assess the repeatability, accuracy and precision of voxel- and region-based CVR measurements at 3 T using a fixed inhaled (FI) CO2 stimulus in a healthy cohort. We simulated the effect of noise, delay constraints and voxel- versus. region-based analysis on CVR parameters. Results were verified in 15 healthy volunteers (28.1±5.5 years, female: 53%) with a test-retest MRI experiment consisting of two CVR scans. CVR magnitude and delay in grey matter (GM) and white matter were computed for both analyses assuming a linear relationship between the BOLD signal and time-shifted end-tidal CO2 (EtCO2) profile. Test-retest repeatability was high (mean [95% CI] inter-scan difference: -0.01 [-0.03,-0.00] %/mmHg for GM CVR magnitude; -0.3 [-1.2,0.6] s for GM CVR delay), but we detected a small systematic reduction in CVR magnitude at scan 2 versus scan 1, accompanied by a greater EtCO2 change (+1.0 [0.4,1.5] mmHg) and lower heart rate (-5.5 [-8.6,-2.4] bpm). CVR magnitude estimates were higher for voxel- versus region-based analysis (difference in GM: +0.02 [0.01,0.03] %/mmHg). Findings were supported by simulation results, predicting a positive bias for voxel-based CVR estimates dependent on tCNR and delay fitting constraints and an underestimation for region-based CVR estimates. In conclusion, BOLD CVR measurements using FI stimulus have good within-day repeatability in healthy volunteers. However, measurements may be influenced by physiological effects and the analysis protocol. Voxel-based analyses should be undertaken with care due to potential for systematic bias; region-based analyses are more reliable in such cases.